Pain relief and associated factors: a cross-sectional observational web-based study in a Quebec cohort of persons living with chronic pain - Zerriouh, Meriem; De Clifford-Faugère, Gwenaelle; Nguena Nguefack, Hermine Lore; Pagé, M. Gabrielle; Guénette, Line; Blais, Lucie; Lacasse, Anaïs (Frontiers in Pain Research, 2024)
Objectives Randomized clinical trials are used to evaluate the efficacy of various pain treatments individually, while a limited number of observational studies have portrayed the overall relief experienced by persons living with chronic pain. This study aimed to describe pain relief in real-world clinical settings and to identify associated factors. Methods This exploratory web-based cross-sectional study used data from 1,419 persons recruited in the community. Overall pain relief brought by treatments used by participants was assessed using a 0%–100% scale (10-unit increments). Results A total of 18.2% of participants reported minimal pain relief (0%–20%), 60.0% moderate to substantial pain relief (30%–60%), and 21.8% extensive pain relief (70%–100%). Multivariable multinomial regression analysis revealed factors significantly associated with greater pain relief, including reporting a stressful event as circumstances surrounding the onset of pain, living with pain for ≥10 years, milder pain intensity, less catastrophic thinking, use of prescribed pain medications, use of nonpharmacological pain treatments, access to a trusted healthcare professional, higher general health scores, and polypharmacy. Factors associated with lower pain relief included surgery as circumstances surrounding pain onset, use of over-the-counter pain medications, and severe psychological distress. Discussion In this community sample of persons living with chronic pain, 8 out of 10 persons reported experiencing at least moderate relief with their treatment. The analysis has enabled us to explore potential modifiable factors as opportunities for improving the well-being of persons living with chronic pain.